LATIHAN BHRAMARI PRANAYAMA (Humming Bee Breath) SEBAGAI UPAYA DALAM MELEPASKAN STRES DI MASA PANDEMI COVID-19 - Ni Luh Ayu Martini; I Gusti Made Widya Sena Widya Sena (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The world is experiencing a tough period since the beginning of 2020 because of the shock of the Corona Virus Disease or Covid-19 phenomenon. Various countries including Indonesia are still struggling to overcome this virus, because the impact is not only on the health sector but also on various other (multidimensional) sectors. Mental health problems that occur during a pandemic can be caused by various things, such as fear of the plague, feeling of isolation during quarantine, sadness and loneliness due to being away from family,stress and confusion due to information. To deal with the symptoms that appear in mental health that emerged during the Covid-19 pandemic, special efforts are needed to be made both individually, in families and in groups. This special effort can be made with pranayama practice. Bhramari pranayama practice (humming bee breath) is a breathing technique in Yoga teachings. This technique is indeed recommended for calming a confused mind or feeling anxious. The purpose of this paper is to describe how to practice bhramari pranayama (humming bee breath) in an effort to release stress during the Covid-19 pandemic. The method used is literature study and various other literature to support the reference of this journal. Bhramari pranayama or what is often called humming bee breath.